Spontaneous aortocaval fistula presenting with acute liver and renal failure: A case report - Mehmet KANBAY,; Gürden GÜR,; Fatih BOYVAT,; Atılay TAŞDELEN,; Sedat BOYACIOĞLU, (Turkish Journal of Gastroenterology, 2019)
-